1986
DOI: 10.1128/jb.168.3.1332-1335.1986
|View full text |Cite
|
Sign up to set email alerts
|

gamma-Glutamyltranspeptidase from Escherichia coli K-12: formation and localization

Abstract: Escherichia coli cells showed maximum activity of y-glutomyltranspeptidase (EC 2.3.2.2) when they were grown at 20°C, 14% of maximum activity at 37°C, and none at 43°C. The enzyme activity of intact cells grown at 20°C was stably maintained after the temperature was changed to 45°C. The activity increased during the exponential phase, and maximum activity was found at stationary phase. Its intracellular localization in the periplasmic space was confirmed.-y-Glutamyltranspeptidase (GGT) catalyzes the hydrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
78
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 34 publications
4
78
0
Order By: Relevance
“…GGT activity was measured by the standard assay method described previously (Suzuki, Kumagai, & Tochikura, 1986b). One unit of the enzyme was defined as the amount of enzyme that released 1 µmol of p-nitroaniline per minute from γ-glutamyl-p-nitroanilide (γ-GpNA).…”
Section: Determination Of Ggt Activitymentioning
confidence: 99%
“…GGT activity was measured by the standard assay method described previously (Suzuki, Kumagai, & Tochikura, 1986b). One unit of the enzyme was defined as the amount of enzyme that released 1 µmol of p-nitroaniline per minute from γ-glutamyl-p-nitroanilide (γ-GpNA).…”
Section: Determination Of Ggt Activitymentioning
confidence: 99%
“…9 ) bacteria. Suzuki et al demonstrated that E. coli K-12 GGT was localized in the periplasmic space 10 ) and supposed that the major function of the enzyme was hydrolysis and not transpeptidation. 6 ) It is known that some strains of Bacillus l1 14) produce poly(y-glutamic acid).…”
mentioning
confidence: 99%
“…There are, however, two notable differences between mammalian and E. coli enzymes. First, the precursor protein of E. coli GGT has a signal peptide at its N-terminal region (13) directing export to the periplasmic space (14), but mammalian GGTs have anchor domains in their N-terminal regions leading to membrane association (15). Additionally, mammalian GGTs are heterologously glycosylated, whereas E. coli GGT is nonglycosylated (2).…”
mentioning
confidence: 99%